A comparative fiqh analysis of hybrid contracts regulation in the Cash Waqf Linked Deposit (CWLD) - Akmal Hidayah; Achmad Arif; Ahmad Muqorobin; Yana Elita Ardiani (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2026)
This study aims to analyze the validity of hybrid contracts in the Cash Waqf Linked Deposit (CWLD) model regulated by the Financial Services Authority (OJK). The study was motivated by the gap between the potential for national cash waqf and the low rate of its actual collection, as well as the fiqh debate regarding the return of principal funds to customers. The method used is a juridical-normative study with a qualitative approach. Data were obtained through a literature review of primary legal sources, including the OJK’s CWLD Implementation Guidelines, Islamic banking regulations, DSN-MUI fatwas, and fiqh literature from the four schools of thought, as well as secondary legal sources such as scientific articles and academic books. The analysis was conducted using a deductive-coherence approach based on the theory of al-‘Uqūd al-Māliyah al-Murakkabah. The results of the study indicate that the CWLD structure falls under the category of al-uqūd al-mujtami‘ah al-mubāhah, which is valid due to the separation of legal objects between the mudārabah investment funds and the endowed returns. A comparative fiqh analysis also confirms the legality of temporary waqf through the talfiq approach, which accommodates the views of the Maliki and Hanafi schools of thought. Thus, the CWLD is an innovation that aligns with the Maqāṣid al-Syarī‘ah while supporting the mobilization of social funds and strengthening the liquidity stability of Islamic banking.